The aggregation study and characterization of silver nanoparticles - Chowdhury, Silvia; Yusof, Faridah; Sulaiman, Nadzril; Faruck, Mohammad Omer (Trans Tech Publications, Switzerland, 2017)
In this article, we have studied the process of silver nanoparticles (AgNPs) aggregation and to stop aggregation 0.3% Polyvinylpyrrolidone (PVP) was used. Aggregation study carried out via UV-vis spectroscopy and it is reported that the absorption spectrum of spherical silver nanoparticles were found a maximum peak at 420 nm wavelength. Furthermore, Transmission Electron Microscopy (TEM) were used to characterized the size and shape of AgNPs, where the average particle size is around 10 to 25 nm in diameter and the AgNPs shape is spherical. Next, Dynamic Light Scattering (DLS) were used, owing to observed size distribution and self-correlation of AgNPs.